Development of a novel enzyme-linked immunosorbent assay for the detection of cytokeratins 5, 8, and 18, and its implications in cervical cancer screening standardization. Issue 2 (21st April 2018) - McNamara, Steven A; Kaufmann, Andreas M; Vasiljeva, Jekaterina; Drechsler, Inka; Luyten, Alexander; Petry, Karl-Ulrich; Chatzistamatiou, Kimon; Agorastos, Theodoros; Soutschek, Erwin; Boecher, Oliver; Koch, Isabel
No abstract available